1983
DOI: 10.1099/0022-1317-64-1-37
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Saimiri-induced Proteins in Lytically Infected Cells. I. Time-ordered Synthesis

Abstract: SUMMARYThe addition of TPA (phorbol-12-myristate-13-acetate) to cultures during the lytic infection with herpesvirus saimiri led to an enhanced and accelerated production of polypeptides induced by H. saimiri and to a rapid shut-down of host cell protein synthesis and allowed a detailed analysis of the protein patterns. Analysis of sequential protein synthesis in owl monkey kidney cells lytically infected with H. saimiri 11 permitted the identification of 31 virus-induced polypeptides. The use of the amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…We did not confirm previous claims that TPA treatment shortened the cycle of virus replication (Modrow & Wolf, 1983) and infection of cells at different stages of the cell-cycle had no consistent effects on the asynchronous expression of the IE 52K protein. Because differences in the rates of many cellular processes would be expected to occur throughout the cell-cycle, we were surprised by the latter result.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…We did not confirm previous claims that TPA treatment shortened the cycle of virus replication (Modrow & Wolf, 1983) and infection of cells at different stages of the cell-cycle had no consistent effects on the asynchronous expression of the IE 52K protein. Because differences in the rates of many cellular processes would be expected to occur throughout the cell-cycle, we were surprised by the latter result.…”
Section: Discussioncontrasting
confidence: 53%
“…It has been suggested that the growth cycle of HVS is advanced in TPA-treated relative to untreated cultures of O M K cells (Modrow & Wolf, 1983). We therefore examined the effects of TPA treatment on the time course of protein synthesis both by an analysis of labelled polypeptides separated from infected cultures by SDS-gel electrophoresis (Fig.…”
Section: Asynchronous Expression Of Hvs Ie 52k In Populations Of Tpa-mentioning
confidence: 99%
“…2a), although it can not be excluded that their presence may simply be due to leakage from nuclei during the subcellular fractionation procedure. A relatively slow and inefficient shut-down of host protein synthesis is also observed following infection by herpesvirus sylvilagus (Patick & Hinze, 1984) and herpesvirus saimiri (Modrow & Wolf, 1983;Randall et al, 1983), the disadvantages of which in the latter case have been partly overcome by the use of phorbol esters (Modrow & Wolf, 1983). Since our major interest has been a description of the nuclear DBPs we have not tried this approach, although a more complete investigation of CTHV-specific protein synthesis may well require such a procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not exhaustively investigated various parameters that might influence optimal growth, the use of various cell types, media, serum concentrations or incubation temperatures did not markedly shorten the growth cycle (unpublished data). The slow growth of CTHV resembles the growth properties of herpesvirus sylvilagus (Patick & Hinze, 1984) and herpesvirus saimiri (Modrow & Wolf, 1983;Randall et al, 1983) in tissue culture. total cell extracts (not shown).…”
Section: Single Cycle Growth: Production Of Infectious Virus and Appementioning
confidence: 99%
“…The specificity of antibodies in the various experimental and natural hosts (Saimiri scireus) was determined by immunoprecipitation of viral polypeptides obtained fiom owl monkey kidney (OMK) cells infected with H. saimiri in the presence of labeled preCursors. Whereas we describe the unglycosylated virus-induced proteins involved in another report [9], we include in this report the description of the glycoproteins in H. saimiri-infected cells.…”
Section: S Modrow H Schmidt and H Wolfmentioning
confidence: 99%